Microbial monitoring and microbial diversity in the EDEN-ISS greenhouse, a test facility for plant-cultivation in space - Gaiser, L.; Beblo-Vranesevic, K.; Engel, D.; Fahrion, J.; Van Houdt, R.; de Chalonge, L.G.; Bunchek, J.M.; Zabel, P.; Schubert, D.; Rettberg, P. (2025)
The limited storage space for consumable goods like food and medicine is one of the major factors currently limiting the duration and distance of crewed spaceflight missions. To overcome these limitations research into bio-regenerative life support systems (BLSS) is being conducted. BLSS utilize the regenerative abilities of plants and microorganisms to provide food, clean water, breathable air and potentially other goods like medicine. Before these technologies can be incorporated they need to be extensively tested and validated on Earth. TheEDEN-ISS project aimed to test plant cultivation technologies for BLSS in a space analogue environment. These technologies were tested in a greenhouse situated at the Neumayer III station in Antarctica for multiple years, to secure an isolated test environment. To ensure the continued operation of a BLSS, it is vital that plants remain healthy, which necessitates the monitoring of the greenhouse microbiome to ensure that pathogens are detected early and counter-measures can be engaged. During different campaigns, swab surface samples were taken from various locations in the greenhouse before/after cleaning and samples taken at regular intervals over an entire growing season. The bioburden of each sample was estimated via viable count and the isolates were identified via partial 16S rRNA gene sequencing. Additionally, 16S amplicon sequencing was performed on DNA extracted directly from the swab-samples to characterize the microbiome. The results revealed that the bioburden of the different sampling positions was not significantly reduced by the cleaning, indicating that the employed cleaning regime was unsuited in its current form to adequately lower the bioburden. Identification of the isolates as well as the full microbiome revealed mostly environmental genera. However, in both cases genera containing potential pathogens were identified. The two sets of sequencing data had little overlap and emphasized different aspects of the greenhouse microbiome, highlighting the ...